If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3(x + -4) = 7(x + -3) Reorder the terms: 6x + 3(-4 + x) = 7(x + -3) 6x + (-4 * 3 + x * 3) = 7(x + -3) 6x + (-12 + 3x) = 7(x + -3) Reorder the terms: -12 + 6x + 3x = 7(x + -3) Combine like terms: 6x + 3x = 9x -12 + 9x = 7(x + -3) Reorder the terms: -12 + 9x = 7(-3 + x) -12 + 9x = (-3 * 7 + x * 7) -12 + 9x = (-21 + 7x) Solving -12 + 9x = -21 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -12 + 9x + -7x = -21 + 7x + -7x Combine like terms: 9x + -7x = 2x -12 + 2x = -21 + 7x + -7x Combine like terms: 7x + -7x = 0 -12 + 2x = -21 + 0 -12 + 2x = -21 Add '12' to each side of the equation. -12 + 12 + 2x = -21 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = -21 + 12 2x = -21 + 12 Combine like terms: -21 + 12 = -9 2x = -9 Divide each side by '2'. x = -4.5 Simplifying x = -4.5
| (6-2c)3c-3=27 | | d^2+11d+18= | | -2y+7=4y-5 | | 20-(x+8)=8x-6 | | (5+x)(5+x)= | | 4w-28+11w+13=180 | | -7(1-x)+15=3(x+8) | | g(x)=x-4 | | -207=-9(-7n+2) | | -2y-16x=14 | | 31x=8x+69 | | 5(8-2)-8(8)=-34 | | 7-(2x-5)=9 | | 65+(10n+6n)=120 | | n^2-2n-63= | | 2+8/c=-10 | | x^2-97x=0 | | 3(-4+-2x+x^2)=0 | | 16=-4x+28 | | 10y+3y-3=24y+30 | | 4n+3(2n-4)=n | | 4m+2(m+1)=23 | | 4-5p=-31 | | -2+18=-x-9 | | 3+2x=3x-4 | | .5+24=3x-46 | | x^16=2 | | (6s^3)+(10s^2)-24s=0 | | 3z+7=32-2z | | 4y^2+22y+24=0 | | 5.1=-8+x | | 40(2a-3)+6=2(5a+43)+20a |